ANALISIS PUTUSAN HUKUMAN MATI MENURUT MAHKAMAH KONSTITUSI NOMOR 2-3/PUU-V/2007 DAN FIQIH SIYASAH - Adem Deni; Abdur Rahim (Jurnal Penelitian Multidisiplin Ilmu, 2022)
The occurrence of pros and cons of the existence of the death penalty in Indonesia for narcotics dealers as a criminal act of capital punishment in the Constitutional Court Decision Number 2-3/PUU-V/2007, thus the author wants to conduct research related to the Analysis of the Death Penalty Decision According to the Constitutional Court Number 2- 3/PUU-V/2007 and Fiqh Siyasah. The purpose of this study was to determine the results of the analysis of the death penalty decision according to the Constitutional Court Number 2-3/PUU-V/2007, and to understand the results of the analysis of the death penalty decision from the perspective of Fiqh Siyasah. This research is a type of library research, where the data sources are obtained from literature searches such as journal articles, internet sites, books, legal materials (laws), and other research results relevant to this research topic. The results of the analysis of the Death Penalty Decision according to the Constitutional Court Number 2-3/PUU-V/2007 are the first, Decision Number 2-3/PUU-V/2007 which contains the death penalty moderation policy is in accordance with the theory of punishment, especially the integrative theory because the Indonesian legal system is a mixture of various legal systems, namely the Dutch legal system, the customary law system, and the Islamic legal system, so that determining a legal policy cannot be separated from these various legal systems, including the influence of international provisions. While the results of the Analysis of the Death Penalty Decision according to Fiqh Siyasah is Islamic law clearly states that the death penalty is a must in the crime of murder. The decision regarding the death penalty is left to each country. In this case, western countries as the originators of the idea of abolishing the death penalty do not impose their will to abolish the death penalty absolutely, including Indonesia.